Reducing information frictions in venture capital: The role of new venture competitions - Howell, Sabrina T. (Journal of Financial Economics, 2020)
Venture capital, an important source of financing for potentially high-growth new businesses, is believed to suffer from information frictions. This paper quantifies the magnitude of these frictions among participants in new venture competitions. In a regression discontinuity design with data from 87 competitions, winning a round increases the chances of external financing by about 35%. Winning is most impactful for ventures that are ranked just above the cutoff but receive no cash prize, and judge ranks strongly predict venture success. The results indicate that these information problems in new venture finance are large, and competitions can help resolve them through certification.